Addressing the Skilled Labor Crisis in Tourism, Hospitality, and Leisure through Human Capital Development - Benya Jariyawijit; Mary Agatha Mozie1; Ononogbo Kingsley Ugochukwu; Angling Widiyanto (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study explores human capital productivity strategies implemented by tourism, hospitality, and leisure business leaders in southern Nigeria to improve employee productivity despite limited access to specialist tourism, hospitality, and leisure educational institutions. Methodology: A qualitative multicase study design grounded in Human Capital Theory was employed. Data were collected through semi-structured interviews with three tourism, hospitality, and leisure industry leaders, site observations, and company documents. Data were analyzed using the modified Stevick-Colaizzi-Keen method with thematic coding and triangulation. Main Findings: Seventeen themes were identified, grouped into challenges, strategies, and business outcomes. Five major strategies improved employee productivity: recruiting workers with strong social capital, enforcing ethical work standards, conducting in-house training, motivating employees through rewards and recognition, and adopting affordable technologies. These strategies enhanced workforce performance, service quality, organizational efficiency, and business sustainability. Novelty/Originality of this study: This study extends Human Capital Theory by demonstrating how tourism, hospitality, and leisure businesses in Nigeria can strengthen workforce productivity without relying on specialist educational institutions, offering practical human capital development strategies applicable to other developing countries and emerging tourism economies.